Factors Influencing Customers’ Borrowing Decisions in Commercial Banks - Kapil Deb Subedi,; Anoj Joshi, (Nepalese Journal of Management Research, 2025)
This study examines the determinants of borrowing decisions of customers in commercial banks using survey responses from 384 participants analyzed through mean, standard deviation, correlation, and multiple regression. The results highlight that bank satisfaction, service quality, interest rates, loan installments, loan covenants, and insurance guarantees significantly impact borrowing behavior, with customer satisfaction and service quality being the most influential. The findings underscore the importance of trust, affordability, and flexibility in shaping borrowing decisions. These insights provide valuable implications for banks to enhance customer experience, policymakers to promote financial inclusion, and researchers to explore borrowing behavior in developing economies further. The study also identifies areas for future research, including the role of digital banking, financial literacy, and sustainable financial products in influencing borrowing behavior.